Mitigating Financial Statement Fraud Through Islamic Professional Ethics in Islamic Microfinance Institutions - Nafisatul Chasanah; Multazam Mansyur Addury (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
This study aims to examine the empirical effect of Islamic professional ethics on the propensity for financial statement fraud within Islamic microfinance institutions in Magelang Regency. Utilizing a quantitative approach, primary data was collected via structured questionnaires from 60 frontline accounting practitioners and analyzed using Ordinary Least Squares (OLS) regression analysis with robust diagnostic screening to ensure the non-violation of classical assumptions. The conceptual framework is anchored in the ethical standards codified by AAOIFI, particularly Amanah, integrity, and professional competence. The research findings demonstrate that Islamic professional ethics exerts a statistically significant negative impact on the operational likelihood of fraudulent financial reporting. Furthermore, field diagnostics reveal a high baseline of cognitive ethical compliance among the surveyed practitioners. These results conclusively indicate that deeply internalized religious values shift accounting choices from mere technical regulations into a vertical act of worship, thereby constructing an effective psychological barrier against manipulative tendencies. This study modifies traditional organizational paradigms by validating a spiritually integrated Divine Social Exchange model to structurally suppress fraud in sharia-based micro-financial institutions. Structurally, these findings imply that management and regulators must formalize AAOIFI-based ethical codification and continuous behavioral training to sustain long-term financial integrity.